Humidity control in different building applications; restaurant and operation theatre - Mustafa, Mohd Syafiq Syazwan (2017)
Air conditioning (AC) in tropical climate required dehumidification of air at a low dew point temperature to meet humidity standard. This increase the required cooling energy and heating energy is needed to raise the supply air temperature to meet the room’s design temperature. This research was carried out to study energy efficiency and indoor environment factor in two different applications that is restaurant and operation theatre (OT). A method was proposed to enhance the humidity control and energy efficiency in the AC system by applying psychrometric analysis based on actual measurement. Three (3) different systems were used in this study that consists of economizer damper, desiccant wheel and heat pipe heat exchanger (HPHX).The economizer damper analysed base on fresh air intake requirement for ventilation purposes on standard ASHRAE 55 (2010). Manufacturing software by Novelaire and HPC were used to perform the psychorometric analysis for desiccant wheel and HPHX. At the restaurant, the grand total loads (Qt) of the existing AC system were 296.1 kW as to meet temperature and humidity level requirement. The Qt was reduced to 153.8 kW for economizer damper, 170 kW with heating 60.38 kW for desiccant wheel and 178.3 kW with heating 4.1 kW for HPHX. In actual measurement for the OT, the existing AC system had a grand total load Qt of 90.1 kW with heating 5.6 kW and it did not meet the humidity level requirement. However, the AC system required Qt 95.9 kW with heating 12.2 kW as to meet the humidity level requirement for an OT. By using the HPHX in the system, a reduced Qt of 81.6 kW with heating 17.7 kW was achieved, where as a Qt of 100.8 kW with heating 39.9 kW was attained by utilizing the desiccant wheel, whilst maintaining the humidity level requirement. The economizer damper was not applicable for the OT because the OT requires 100% fresh air intake. As a conclusion, damper economizer was beneficial for energy efficiency in restaurants with reducing of 48% energy used and HPHX was beneficial for energy efficiency with reduced 9.4% in OT compared with existing AC system.